Extrapulmonary Comorbidities Associated with Chronic Obstructive Pulmonary Disease: A Review - Xiang Y; Luo X (International Journal of COPD, 2024)
Yurong Xiang,1,* Xiaobin Luo2,* 1School of Medical and Life Science, Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan, 610000, People’s Republic of China; 2Department of Respiratory and Critical Care Medicine, Suining Central Hospital, Suining, Sichuan, 629000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaobin Luo, Department of Respiratory and Critical Care Medicine, Suining Central Hospital, Suining, Sichuan, 629000, People’s Republic of China, Tel +86-18008258560, Email lxb19720923@163.comAbstract: Most patients with chronic obstructive pulmonary disease (COPD) suffer from at least one additional, clinically relevant chronic disease. To a degree, the high global prevalence and mortality rate of COPD is closely related to its extrapulmonary effects. Moreover, the various of comorbidities of COPD and itself interact with each other, resulting in diverse clinical manifestations and individual differences, and thus further influencing the prognosis as well as healthcare burden of COPD patients. This is closely related to the common risk factors of chronic diseases (aging, smoking, inactivity, etc.). Additionally, some pathophysiological mechanisms caused by COPD, including the systemic inflammatory response, hypoxia, oxidative stress, and others, also have an impact on other systems. But comprehensive management and medical interventions have not yet been established. The clinicians should improve their knowledge and skills in diagnosing as well as treating the comorbidities of COPD, and then aim to develop more individualized, efficient diagnostic and therapeutic strategies for different patients to achieve greater clinical benefits. In this article, we will review the risk factors, mechanisms, and treatment strategies for extrapulmonary comorbidities in chronic obstructive pulmonary disease, including cardiovascular diseases, diabetes, anemia, osteoporosis, emotional disorders, and gastroesophageal reflux disease.Keywords: chronic obstructive pulmonary disease, comorbidity, risk factors, therapeutics